Efficacy of biologics for the treatment of periodontal infrabony defects: An American Academy of Periodontology best evidence systematic review and network meta‐analysis - Tavelli, Lorenzo; Chen, Chia‐Yu (Jennifer); Barootchi, Shayan; Kim, David M. (Journal of periodontology (1970), 2022)
Background A large variety of biomaterials, biologics and membranes have been utilized in the past 40 years for the regenerative treatment of periodontal infrabony defects. Biologic agents have progressively gained popularity among clinicians and are routinely used for periodontal regeneration. In alignment with the goals of the American Academy of Periodontology (AAP) Best Evidence Consensus (BEC) on the use of biologic mediators in contemporary clinical practice, the aim of this sytematic review was to evaluate the effect of biologic agents, specifically autogenous blood‐dervied products (ABPs), enamel matrix derivative (EMD) and recombinant human platelet‐derived growth factor‐BB (rhPDGF‐BB), on the regenerative outcomes of infrabony defects. Methods A detailed systematic search was conducted to identify eligible randomized control trials (RCTs) reporting the outcomes of periodontal regenerative therapy using biologics for the treatment of infrabony defects. A frequentist mixed‐modeling approach to network meta‐analysis (NMA), characterized by the assessment of three individual components for the treatment of an infrabony defect (the bone graft material [BG], the biologic agent, the application of a barrier membrane) was performed to evaluate and compare the relative efficacy of the different components, on the outcomes of different therapeutic modalities of periodontal regeneration. Results A total of 153 eligible RCTs were included, with 150 studies contributing to the NMA. The quantitative analysis showed that the addition of biologic agents to bone graft significantly improves the clinical and radiographic outcomes, as compared to BG and flap procedures alone. Barrier membranes enhanced the regenerative outcomes of BG but did not provide further benefits in combination with biologics. The type of BG (autogenous, allogeneic, xenogeneic or alloplastic) and the biologic agent (EMD, platelet‐rich fibrin [PRF], platelet‐rich plasma [PRP] or rhPDGF‐BB) played a significant role on the final outcomes of infrabony defects. Allogeneic and xenogeneic BGs exhibited statistically significantly superior clinical gain than synthetic and autogenous BGs (p < 0.05 in all the comparisons), while rhPDGF‐BB and PRF demonstrated significantly higher stability of the gingival margin (p < 0.01) and radiographic bone fill/gain (p < 0.05), together with greater, although not statistically significant, clinical attachment level gain and pocket depth reduction, than EMD and PRP. Overall, rhPDGF‐BB exhibited the largest effect size for most parameters, including clinical attachment level gain, pocket depth reduction, less gingival recession and radiographic linear bone gain. Considering the relatively high number of trials presenting an unclear or high risk of bias, the strength of recommendation supporting the use of PRP was judged weak, while the recommendation for EMD, PRF and rhPDGF‐BB was deemed in favor. Conclusions Biologics enhance the outcomes of periodontal regenerative therapy. Combination therapies involving BGs + biologics or BGs + barrier membrane demonstrated to be superior to monotherapies. The choice of the type of BG and biologic agent seems to have significant impact on the clinical and radiographic outcomes of infrabony defects.